A contextualised Internationalisation of the curriculum: A case study in China - Li, Qi; Li, Dongmei; Wu, Jianli (Journal of University Teaching and Learning Practice, 2024)
China is often seen as a home country of international students in higher education internationalisation. Little is known how Chinese institutions actively engage in multi-modal and multi-lateral internationalised practices. This paper offers an updated insight of higher education internationalisation in a context outside the dominant western landscape through a case study set in an international college in China. Making use of the existing frameworks of internationalisation of the curriculum (IoC), the current case study focuses on three key aspects of the curriculum: program development, student experience and staff perspectives. A mixed-method approach was used to collect data from three sources: institutional archives and course materials, and student and staff surveys. Triangulated data show that the curriculum was well aligned within the existing IoC frameworks. The curriculum incorporated international content and comparative approaches. Local socio-cultural values were also embedded in joint programs. Both students and academics’ perspectives of an internationalised curriculum showed a high level of alignment with the western community. Student and staff data also revealed urgent need to enhance the level of internationalisation, including English competence of discipline academics, people-to-people connection between local Chinese students and incoming international students, student and staff mobility opportunities, and teaching and research development for academic staff. This study hopes to contribute to the current knowledge of internationalisation of the curriculum with updated understanding in a Chinese context. This paper also provides insight in internationalisation implemented at the curriculum level in China, a context that presents much difference from but relates closely with the western context.